Identifying Differences in Nutrition‐Related Learning Interests of Adolescent Students. (1st February 2021) - Miller, Margaret; Barwood, Donna; Furfaro, Michael; Boston, Julie; Smith, Sandra; Masek, Martin
ABSTRACT: BACKGROUND: In this study, we examined nutrition‐related topics among adolescent students attending schools with different Indices of Community Socio‐Educational Advantage (ICSEA). METHOD: Participating students (N = 206) from 5 schools in Western Australia completed a paper‐based questionnaire on nutrition‐related topics. Frequencies and independent chi‐square tests were used to identify differences between sexes and school ICSEA. RESULTS: Of the participating students, 75% were interested in learning about 8 of 16 topics. We found statistically significant differences by sex (p < .01) for "Eating the right foods for preventing illness and disease, " "Eating the right food for being active" among girls, and "Reducing food waste" among boys. We also noted differences by school ICSEA. CONCLUSION: Acknowledging sex and socioeducational differences in teaching and learning may help teachers to engage adolescent students in nutrition education.